Barriers to the development of affordable housing on well-located land: A qualitative study of planning regulations and by-laws in Cape Town - Briel, Sofia (Faculty of Engineering and the Built Environment, 2023)
The notion of adequate housing considers the economic, political, and social components of housing which in Cape Town translates to housing that is well located, affordable, and accessible and creates urban place-making. Both state-subsidised and private development has failed to deliver adequate housing in Cape Town, exacerbating an existing housing and affordable housing shortage and perpetuating spatial inequality in the city. Planning system plays a dynamic role in enabling adequate housing. It is important to distinguish between planning systems that ‘control' and ones that are ‘flexible'. This study critically explores the role of planning regulations and by-laws in the development of adequate housing by means of state-subsidised and other housing instruments. The case of the City of Cape Town's planning regulations, related by-laws and housing policies is the source of ethnographic, empirical findings. These qualitative findings have been generated by way of interviews – with professional planners working in the public and private sectors as well as members of nongovernmental organizations concerned with housing and development in Cape Town – and analysis of planning regulation and policy documentation and secondary data from media sources. A theoretical framework consisting of literature on well-located, affordable, and accessible housing, and the nature and role of planning systems in relation to adequate housing, is the basis of the analysis and synthesis of the research findings. This case study shows that in Cape Town elements of the planning regulations and by-laws act as barriers to the development of adequate affordable housing. But it is not simply the existence of these elements that is the issue. How the planning regulations and by-laws as well as other planning systems are used is also of importance. Non-statutory planning tools address adequate affordable housing to a greater degree than the regulations and by-laws, however, these tools have weak paths to implementation within the current planning systems. So, while the intentions and ideas pertaining to adequate housing do exist to a certain degree in the planning systems, there is a gap in implementation. Additionally, multiple barriers outside of the domain of the planning regulations and by-laws emerged from the findings. Overall, this study indicates that aspects of the planning regulations and by-laws are hindering the development of affordable housing in Cape Town. However, they are but one of many barriers to the development of adequate housing on well-located land in the city.